Pusat Informasi dan Penjualan Mobil Lamborghini di Surabaya - Wijaya, Julianto Wicaksono (Intra, 2014)
The sales information center and community devoted to the Lamborghini car lovers in Surabaya area. Its design concept is to get to know the place where intended, understand history as well as spare parts sales, car servicing lambhorghini and provide a gathering place for community lambhorghini car in Surabaya and surrounding areas. Facilities that will be made include receptionist, showroom area, service area, cafÃ©, lounge, multipurpose room and toilet. It is developed by bringing together all the facilities for the lovers or people who want to know about a car lambhorghini in Surabaya